2017
DOI: 10.5194/tc-11-2175-2017
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on post-depositional isotope modifications in East Antarctic firn from analysing temporal changes of isotope profiles

Abstract: Abstract. The isotopic composition of water in ice sheets is extensively used to infer past climate changes. In lowaccumulation regions their interpretation is, however, challenged by poorly constrained effects that may influence the initial isotope signal during and after deposition of the snow. This is reflected in snow-pit isotope data from Kohnen Station, Antarctica, which exhibit a seasonal cycle but also strong interannual variations that contradict local temperature observations. These inconsistencies p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 50 publications
5
71
0
Order By: Relevance
“…The snow trench (T15) isotope data are available in the PANGAEA repository https://doi.org/10.1594/PANGAEA.876639 (Münch et al, 2017b). The snow-pit and firn-core isotope data used are available in the PANGAEA repository https://doi.org/10.1594/PANGAEA.883787 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The snow trench (T15) isotope data are available in the PANGAEA repository https://doi.org/10.1594/PANGAEA.876639 (Münch et al, 2017b). The snow-pit and firn-core isotope data used are available in the PANGAEA repository https://doi.org/10.1594/PANGAEA.883787 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the snow is transported to the surface by precipitation where it is redistributed and mixed by wind, giving rise to the surface isotope signal δ 18 O surface (t). Finally, the surface signal is buried in the firn column which is accompanied by diffusional smoothing of the signal and densification of the layers (Münch et al, 2017a). Analysing a snow pit or firn core during this process then represents a snapshot of the firn isotope signal δ 18 O firn (z).…”
Section: Minimal Forward Model For Vertical Isotope Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the observed low temporal δ/ T may reflect a strong gradient between condensation and surface temperature in winter (Ekaykin et al, ; Landais, Ekaykin, et al, ) and/or the vanishing inversion layer in summer (Landais et al, ). In the central Antarctic Plateau with very low snow accumulation rates (0.016–0.038 m/w.e.a; Ekaykin et al, ; Hou et al, ; Jouzel et al, ; Masson et al, ; Watanabe et al, ), postdepositional processes could significantly modify the isotopic composition of surface snow (Casado et al, ; Laepple et al, ; Münch et al, ; Ritter et al, ). Recent observations in the summer have revealed that the isotopic composition of surface snow in the absence of precipitation varies with changes of the surface vapor isotopic composition (Casado et al, , ; Ritter et al, ; Steen‐Larsen, Masson‐Delmotte, et al, ; Touzeau et al, ), suggesting possible isotopic exchange between surface snow and atmospheric water vapor in the polar regions.…”
Section: Introductionmentioning
confidence: 99%